Pelatihan Pembuatan Makanan Anti Stunting untuk Anak di Kampung Nelayan Tambak Rejo - Windy Rizkaprilisa; Martina widhi Hapsari; Novia Anggraeni; Paulus Damar Bayu Murti; Anggara Mahardika (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
This public service activity was order to “Ayo Siaga Bencana Dapur Umum Cegah Stunting” in Kampung Nelayan Tambak Rejo. Kampung Nelayan Tambak Rejo was affected area by flooding due to high tides and beach abrasion, so the childrens can be affected stunting. This program aimed to educate parents about stunting prevention by providing nutritious anti-stunting food and training to make anti-stunting food. This activity consists of three stages: providing education about stunting prevention; training to make anti stunting food and distributing it to the citizens. Parents and children were very enthusiastic when tasted "Bola-bola Ubi Ikan Lele". It were made from nutritious ingredients that were easily to get and affordable price. Education about stunting prevention can be applied in their environment and training about making anti-stunting food can be an idea for food to be given to children.